Liquid-Liquid Interfacial Electron Transfer from Ferrocene to Gold(III): An Ultrasimple and Ultrafast Gold Nanoparticle Synthesis in Water under Ambient Conditions - Ciganda, Roberto; Irigoyen, Joseba; Gregurec, Danijela; Hernandez, Ricardo; Moya, Sergio; Wang, Changlong; Ruiz, Jaime; Astruc, Didier (Inorganic Chemistry, 2016)
Ferrocene (Fc) in ether reduces HAuCl4 in water within seconds under ambient conditions in air upon stirring, forming ferricinium chloride stabilized water-soluble 20 nm gold nanoparticles (AuNPs) that are redispersible in the presence of poly(N-vinylmethylpyrrolidone) or NaBH4 + thiol. After reduction with NaBH4 yielding Fc and 26 nm sodium poly(hydroxyborate) stabilized AuNPs, the core size no longer changes following reactions with thiols providing (RS)nAuNPs.
CRIS-Team Scopus Importer:2020-10-13